Risk Management and Sustainability Performance Research Map: A comprehensive Bibliometric analysis - Widaryanti, Widaryanti; Wan Abdullah, Wan Amalina; Sitawati, Riana (International Journal of Indonesian Business Review, 2025)
Purpose – This study aims to investigate research trends and patterns in the field of risk management and sustainability performance using bibliometric analysis methods.Methodology/approach – By utilizing the Scopus database from 2000- 2024, we collect data from relevant articles and conduct analysis of keywords, authors, journals, and institutional affiliates. To address this issue, our critical review examined 677 articles discussing research on risk management and sustainability. The analysis tools used for bibliometric analysis are Biblioshiny and Vos Viewer.Findings – The results of the analysis show that there are eight main clusters covering various related aspects, such as corporate sustainability, supply chain management, environmental management, disaster risk management, credit risk management and green economy, business competition, decision management, and sustainable entrepreneurship. Each cluster is analyzed in depth to identify the contribution and relationship between the variables involved.Novelty/value – These findings provide a comprehensive understanding of the current research landscape and point to potential directions for future research in the field of risk management and sustainability. This research also emphasizes the importance of a cross- disciplinary approach in addressing global sustainability challenges